2021
DOI: 10.1121/10.0006658
|View full text |Cite
|
Sign up to set email alerts
|

Three psychophysical metrics of auditory temporal integration in macaques

Abstract: The relationship between sound duration and detection threshold has long been thought to reflect temporal integration. Reports of species differences in this relationship are equivocal: some meta-analyses report no species differences, whereas others report substantial differences, particularly between humans and their close phylogenetic relatives, macaques. This renders translational work in macaques problematic. To reevaluate this difference, tone detection performance was measured in macaques using a go/no-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…The effects of duration in this study extend work on auditory temporal integration to an AM discrimination paradigm, as opposed to more common tone detection paradigms (Costalupes, 1983; Heil et al, 2017; Mackey et al, 2021a; O’Connor et al, 1999; Plomp and Bouman, 1959). Temporal integration of AM stimuli has been explored almost exclusively at the psychophysical level, and mostly in humans (Dau et al, 1997; Lee, 1994; O’Connor et al, 2011; Sheft and Yost, 1990), though one study has reported causal evidence that parietal cortex is involved (Yao et al, 2020).…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…The effects of duration in this study extend work on auditory temporal integration to an AM discrimination paradigm, as opposed to more common tone detection paradigms (Costalupes, 1983; Heil et al, 2017; Mackey et al, 2021a; O’Connor et al, 1999; Plomp and Bouman, 1959). Temporal integration of AM stimuli has been explored almost exclusively at the psychophysical level, and mostly in humans (Dau et al, 1997; Lee, 1994; O’Connor et al, 2011; Sheft and Yost, 1990), though one study has reported causal evidence that parietal cortex is involved (Yao et al, 2020).…”
Section: Discussionmentioning
confidence: 56%
“…However, psychophysical studies have gained insight into auditory temporal integration by manipulating duration in AM processing tasks (Dau et al, 1997; Lee, 1994; O’Connor et al, 2011; Sheft and Yost, 1990). This question is of particular importance in the context of macaque studies, as macaques and budgerigars may exhibit unique similarity to humans in temporal integration (Mackey et al, 2021a). This motivated us to evaluate the effects of duration on performance in the AM frequency discrimination task previously discussed and explore its neural correlates.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations